Increased QT interval variability in 3 recently concussed athletes: an exploratory observation - La Fountaine, M. F.; Gossett, J. D.; de Meersman, R. E.; Bauman, W. A. (Journal of Athletic Training, 2011)
Context: The QT interval variability index (QTVI) is a noninvasive measure of beat-to-beat fluctuations of the QT interval as seen from a single electrocardiographic lead. It represents the relationship between the respective variabilities of the QT and R-R intervals. Recently, the QTVI was demonstrated to be an index of vagal cardiac autonomic modulation in resting conditions.